Impact of the Family Planning Association of Sri Lanka's contraceptive social marketing on the National Family Planning Programme (2001-2020): Is there an effect ofCOVID-19? - M. Suchira S. Suranga; Indralal W. De Silva; Malith Kumarasinghe (College of Community Physicians of Sri Lanka, 2021)
Introduction: The global first national level social marketing programme (SMP) implemented by a nongovernmental organization was started in Sri Lanka on 1973 by The Family Planning Association of Sri Lanka. After four decades, this operation has grown to be the market leader of contraceptives, distributing over 15 products through 4867 pharmacies island wide. In 2020, despite the COVID-19 pandemic and other related challenges, it generated 367 442 couple years of protection (CYP).   Objectives: To assess the impact and contribution of SMP to the National Family Planning Programme (NFPP) during the past two decades with a special focus on the effect of the COVID-19 pandemic in 2020.   Methods: The product-wise annual sales figures of the SMP during past two decades (2001-2020) were analyzed using Marries Stop International Impact2 Calculation Tool (MSI-Impact2) to estimate the impact and contribution to the NFPP. The programme data published in the Annual Report of the Family Health Bureau was used to compare and triangulate the results obtained from MSI-Impact2.   Results: Contribution of the SMP to the national modem contraceptive prevalence rate (mCPR) during the past two decades is 10-1 7%. The SMP averts over 40 000 unsafe abortions, 15 maternal deaths and 60 child deaths annually. Although the national level impact of COVID-19 on contraceptive SM is negligible, a significant shift in the contraceptive purchasing pattern was observed in 2020.   Conclusions & Recommendations: SM of contraceptives has contributed to improving women's health significantly in Sri Lanka. In the absence ofSMP, the country mCPR would have been reduced by 10-17%.